The type argument in essays of student stage formal operation - Ulfah Mey Lida (Indonesian Reseacher for Language Learning and Teaching, 2024)
Argument of course no could free of the thought process. Thought that process as something gradual development from think intellectual concrete to abstract sequentially through four period. Study this aim for describe type argument in essay argument student Step formal operations. This study was conducted using a descriptive qualitative approach. Collected data in the form of essay argument student Step formal operations in SMP, SMA, and SMK. Source of this data obtained from Duty student write the arguments that have been given by their teacher. In accordance with research data, instruments used in the form of data card. Research data analysis this using analytical model contents communication Holsti. Based on results analysis type argument in essay argument student Step this formal operation could concluded that type argument stance, argument proof and argument conclusion used by varied by students Step formal operations. Based on analysis that has been done, founded 5 types argument used by student Step formal operations in essay argument.